Identifying the Qualities needed for a Virtual Learning Space in Communication and Information Technology Skills - Harris, Rachel A.; Pereira, Márcia A.; Davidson, Duncan (Proceedings of the International Conference on Networked Learning, 2000)
Staff development in Communication and Infom1ation Technology (C&IT) is one of the major challenges currently facing educational institutions. In addition, while being asked to provide support for a ' lifelong learning' society (Dearing, 1997), higher education institutions look to the implementation of C&IT as a means of supporting developments in this area. C&IT staff development is thus all the more crucial, as identified by the Dearing Repo,1 itself, and others (Milligan, 1999; Atkins, 1998 ). This paper presents ongoing research and development chat will support educational institutions in facing these challenges via the development of a Virtual Learning Space (VLS) for C&IT staff development.